MOLECULAR DOCKING VIRTUAL SCREENING, DRUG-LIKENESS AND PHARMACOKINETICS (ADMET) PROPERTIES PREDICTION OF SOME ENDOMETRIAL CANCER AGENTS - Aiyedogbon, Okikiola; Ibrahim, Muhammad Tukur; Adamu Shallangwa, Gideon; Muhammad Tahir, Salisu; Abubakar, Tukur (FUDMA JOURNAL OF SCIENCES, 2022)
Endometrial or uterine cancer is a malignancy arising from the endometrium of the uterus. Women have a 1 in 40 life-time risk of being diagnosed with endometrial cancer, the fourth most common maligÂ¬nancy among women. Endometrial cancer is the most common gynecological malignancy in the developed world. The binding mode of some endometrial cancer agents in the active site of human estrogen receptor (PDB1*1P) (receptor) was studied via molecular docking. Molecule 6 was identified to have the highest binding energy of -10.1 kcal/mol among other selected compounds which might be as a result of hydrogen bond interactions formed with ASP480 amino acid residues and hydrophobic/other interactions formed with LEU508, LEU479 and ILE451 amino acid residues in the active site of the receptor. The drug-likeness properties of these selected endometrial cancer agents were predicted following the Lipinskiâ€™s rule of five and were found to be orally active and bioavailable as they obeyed the used filtering criterion. Based on the pharmacokinetic properties predicted, they were seen to have good ADMET properties. This research proposed a way for designing potent endometrial cancer agents against their target enzyme (human estrogen receptor).